Futuristic VR image presentation technique for better mobile commerce effectiveness - Park, Jiseob; Choi, Junho; Rhee, Cheul (Virtual Reality, 2021)
Previous studies show that VR images can influence consumers’ attitudes and behaviors by evoking imagination. In this study, we introduce a reality-based closed-loop 3D image (hereafter Virtualgraph). Then, we try to see whether such image would increase evocativeness in a mobile commerce environment and whether higher telepresence of the visual image of a product can increase the purchase intention of that product. In order to find the above, we developed a model comprised of constructs containing telepresence, perceived value price, perceived food quality, and vividness of visual imagery questionnaire (VVIQ). We used Virtualgraph application to conduct an experiment and then conducted an interview as well as a survey. As results of the experiment, survey, and interview, we found the followings. First, users evoke imagination better with Virtualgraph than with still images. Second, increased evocativeness affects purchase intention if the perceived quality of fresh food product is satisfactory. Third, increased evocativeness makes users value products higher and do even much higher when the perceived quality of fresh food product is good. From the interview, we could find that the experimental group had higher purchase intentions and perceived products as more expensive ones. Also, they perceived images of products clearer and more vivid than did the control group. We also discuss the strategic implications of using Virtualgraph in mobile shopping malls.
Keywords: Control groups; Experimental groups; Image presentations; Mobile shopping; Perceived quality; Perceived value; Purchase intention; Visual imagery; Evocativeness; Guided imagery; Reality-based closed-loop 3D image; Telepresence; Virtualgraph; VR contents; VR images